Situation Report: Hungary, 10 October 1967 - Radio Free Europe/Radio Liberty Research Institute (RFE/RL Research Institute)
An information bulletin produced by Radio Free Europe based on extensive monitoring of communist bloc news outlets and primarily intended for internal circulation. Pieces were generally contributed by the staff of the research and analysis departments and treated current affairs in the region. Unfavorable Development of Hungarian-West German Economic Relations Closing Down the Agricultural Machine Stations Improved Supply of the Household Plots with Small Machines Intensification of Austro-Hungarian Economic Relations More Aid to North Vietnam Hungarian Loan to Sudan Hungarian Deputy Ministers Dismissed Cardinal König Visits Cardinal Mindszenty